Demographic characteristics and disease severity associated with IgA/IgG deposition patterns in autoimmune bullous diseases: a cohort study based on a registry database - Li, Jishu; Feng, Xun; Wang, Mi; Liu, Hongjie; Yang, Mei; Pang, Jiyun; Zou, Min; Xiao, Yue; Zhang, Xiwen; Hu, Hongxiang; Zhou, Yuxi; Alqusseireen, Yazan Moufaq; et al. (Frontiers in Immunology, 2025)
BackgroundDirect immunofluorescence (DIF) microscopy is the gold standard for diagnosing autoimmune bullous diseases (AIBDs), but the clinical significance of IgA and IgG co-deposition was unclear.ObjectiveInvestigate the demographic differences and disease severity among different IgG/IgA deposition patterns in DIF.MethodsWe conducted a retrospective cohort study based on a registry database that analyzed demographic data, involvement sites, and immunofluorescence patterns of patients with DIF biopsy. Patients were categorized into intercellular (group A) and basement membrane zone (group B) deposition patterns. Logistic regression models assessed associations between deposition status and demographic characteristics. Disease severity and prognosis were analyzed retrospectively through subgroup analyses.ResultsIn group A, female gender (OR = 1.665, P = 0.011) and stronger IgG deposition (OR = 3.881, P < 0.001) were associated with IgA and IgG co-deposition. In group B, female gender (OR = 1.382, P = 0.002), stronger IgG deposition (OR = 2.673, P < 0.001), and mucosa tissue (OR = 3.052, P < 0.001) were associated with IgA and IgG co-deposition. IgA and IgG co-deposition in group A was associated with higher Pemphigus Disease Area Index scores (P = 0.036), while in group B, it correlated with mucosal involvement (P = 0.007). No differences in the proportion of disease severity scores improvement after 6 months of standard treatment were found in both groups.ConclusionsFemale gender, stronger IgG deposition, and mucosa tissue are key factors affecting IgA and IgG co-deposition in AIBD patients. For clinical correlation, patients with IgA and IgG co-deposition in pemphigus exhibit more severe disease severity compared with those with IgG deposition only, while patients with co-deposition in pemphigoid are more prone to mucosal involvement.